Physico-Chemical Analysis of Water at Selected Point in Kota, Rajasthan - Chouhan, Rajeev K; Bansal, Anil K; Chhipa, R C (Journal of Drug Delivery and Therapeutics, 2019)
Water is the basic unit of life and it is essential element for all living forms and the environment health. Water is the basic unit of life and it is essential element for all living forms and the environment health. Rivers are essential for all living organism on earth. In this study, we screened the point of contamination of pollutants in Chambal river water and their concentration in different season.  Present study revealed that water quality parameters (pH, EC, Chloride, Fluoride, TDS, DO, COD, BOD etc) of some sample site showed contamination and depletion in quality of Chambal River in pre monsoon. The water quality was maintained in certain sample site and all parameters were found under limit. We should maintain quality of water because Chambal River is major source of drinking water for districts of Rajasthan.Keywords: Water quality, Chambal River, Chemical parameter